2020
DOI: 10.3390/ijerph18010256
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Role of Different Instructional Designs When Learning Tactical Scenes of Play through Dynamic Visualizations: A Systematic Review

Abstract: Dynamic visualizations such as videos or animations have been developed to exchange information that transforms over time across a broad range of professional/academic contexts. However, such visual tools may impose substantial demands on the learner’s cognitive resources that are very limited in current knowledge. Cognitive load theory has been used to improve learning from dynamic visualizations by providing different instructional designs to manage learner cognitive load. This paper reviews a series of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
3
8
0
Order By: Relevance
“…In line with the first hypothesis, the results showed that the video modeling does not lose its effectiveness in learning basketball tactical actions (whatever the gender of the learners), despite the addition of arrow-symbols which can allow learners to improve motor learning from static pictures [24,51]. These results are in line with a consistent body of research carried out either in sports or in other instructional domains, showing the positive effects of dynamic visualizations in learning when the content to be learnt is realistic and involves procedural motor knowledge [20,21,24,52]. Consequently, the human movement effect [27] has again been supported in learning sport skills requiring the whole body, indicating that video modeling examples were found to be within the working memory constraints of the students, and were not too long and/or complex to become subject to transient effects (see Wong et al [14] for a discussion of how the transient nature of digital videos can sometimes hinder motor learning).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In line with the first hypothesis, the results showed that the video modeling does not lose its effectiveness in learning basketball tactical actions (whatever the gender of the learners), despite the addition of arrow-symbols which can allow learners to improve motor learning from static pictures [24,51]. These results are in line with a consistent body of research carried out either in sports or in other instructional domains, showing the positive effects of dynamic visualizations in learning when the content to be learnt is realistic and involves procedural motor knowledge [20,21,24,52]. Consequently, the human movement effect [27] has again been supported in learning sport skills requiring the whole body, indicating that video modeling examples were found to be within the working memory constraints of the students, and were not too long and/or complex to become subject to transient effects (see Wong et al [14] for a discussion of how the transient nature of digital videos can sometimes hinder motor learning).…”
Section: Discussionsupporting
confidence: 79%
“…In this context, examining the effectiveness of video modeling vs. static pictures in learning different motor skills has raised considerable interest among sport didacticians/psychologists [20]. These scientific works dovetail nicely with findings from observational learning research.…”
Section: Introductionmentioning
confidence: 93%
“…However, in the case of a complex material, highlighting game actions through coordinated visual and verbal cues was effective for improving tactical learning: participants achieved a higher level of immediate and delayed recall performances. First, these results could fit with some studies carried out in either team sports or in other instructional domains, indicating that instructional design techniques (e.g., employing self-control, decreasing the presentation speed) are only effective with the increase in the complexity of instructional materials [ 34 , 35 , 36 , 37 , 38 ]. For example, Rekik et al [ 1 ] showed that a sequential presentation of information (either with or without tracing) improves tactical learning solely when processing complex soccer diagrams.…”
Section: Discussionsupporting
confidence: 62%
“…In the area of indoor map representation, many research results have also been achieved in recent years. Reference [23] proposed a method for displaying and navigating indoor location maps by using a mobile terminal with a camera to superimpose path information on a paper map. Reference [24] proposed an indoor access representation method that can represent the topological relationship of cross-floor access from the perspective of underground pipeline maps.…”
Section: Indoor Map Representationmentioning
confidence: 99%